Mucopolysaccharidosis type I, II and VI and response to enzyme replacement therapy: Results from a single-center case series study - Franco, José Francisco da Silva; El Dib, Regina [UNESP]; Agarwal, Arnav; Soares, Diogo; Milhan, Noala Vicensoto Moreira [UNESP]; Albano, Lilian Maria José; Kim, Chong Ae (International Research and Cooperation Association for Bio & Socio-Sciences Advancement (IRCA-BSSA), 2017)
Mucopolysaccharidoses (MPS) types I, II and VI are associated with deficiencies in alpha- L-iduronidase, iduronate-2-sulfatase and N-acetylgalactosamine-4-sulfatase, respectively, and generally involve progressive and multi-systemic clinical manifestations. Enzyme replacement therapy (ERT) appears to be reasonably well tolerated. The aim of this study was to examine clinical and diagnostic findings of a series of pediatric and adult MPS patients, and assess the safety and efficacy of ERT in children and adults with MPS type I, II and VI. Pediatric and adult patients were treated weekly with 1 mg/kg recombinant human N-acetylgalactosamine-4-sulphatase (rhASB), 0.45 mg/kg alpha-L-iduronidase, or 0.5 mg/kg iduronate-2-sulfatase. Clinical and biochemical parameters with ERT were evaluated for a mean duration of 5 years. Mantel-Haenszel risk ratios and associated 95% confidence intervals (CIs) were calculated for rates of death among different types of enzyme replacement therapies (ERTs). Twenty-seven patients (mean ages - pediatric: 6.8 years; adult: 29 years) were included. ERT was found to be consistently well tolerated and effective in attenuating symptoms, but did not prevent the progression of the disease or reduce mortality rates. Our findings demonstrated that early diagnosis and initiation of ERT are critical for improvements in patient-important outcomes and quality of life, although disease progression and mortality rates remain high.
Keywords: Glycosaminoglycans; Lysosomal storage disorders; Prognosis; Treatment